Estimation of Performance Characteristics of Analytical Methods for Mycobacterium avium subsp. paratuberculosis Detection in Dairy Products - Butot, Sophie; Ricchi, Matteo; Sevilla, Iker A.; Michot, Lise; Molina, Elena; Tello, Maitane; Russo, Simone; Arrigoni, Norma; Garrido, Joseba M.; Tomas, David (Frontiers in Microbiology, 2019)
Paratuberculosis is a chronic enteric infection, caused by Mycobacterium avium subsp. paratuberculosis (MAP), affecting virtually all ruminants as well as other animals. MAP is also suspected to be involved in the etiology of some human diseases, like Crohn’s disease and others. In surveillance studies, different analytical methodologies were employed to detect MAP, showing different results and incidence in dairy products. The aim of this study was to evaluate the performance characteristics of three analytical methods (culture, quantitative PCR (qPCR) and peptide-mediated magnetic separation (PMS) phage-based assay) for MAP detection in raw, heat-treated and powdered milk. The methods were evaluated according to performance characteristics defined for qualitative methods in ISO 16140-2:2016. To estimate sensitivity (including trueness) and LOD, 720 and 900 test portions, respectively, were blind tested by two laboratories. Considering all matrices, different sensitivities, expressed as the percentage of positives from the total of true positive test portions, were obtained for IS900 qPCR (94 %), f57 qPCR (76 %), culture (83 %) and PMS-Phage (40 %). Trueness, expressed as results correctly assigned (including positive and negative) to the reference value, was 93 % for the IS900 qPCR method, 89 % for culture and 49 % for the PMS-phage. The LODs obtained in this study were similar to the LODs previously published for cultural and qPCR methods. However, for the PMS-Phage method, the obtained results showed higher LOD values compared to the limited data available in the scientific literature. Our results highlight that while the PMS-Phage assay is workable in pure liquid culture for estimation of MAP counts, its usage for surveillance of dairy matrices should be treated with a lot of caution as performance characteristics obtained were lower than for the two other methods tested. qPCR and culture are the most appropriate methods to detect MAP in milk-based matrices according to ISO 16140 methodology. Cultural techniques are considered the gold standard for detection of viable MAP, but qPCR, which is widely used in analytical and surveillance studies, can be considered a suitable and recommendable alternative to cultural methods for screening, if confirmation of MAP’s viability is not requested.